A longitudinal examination of mothers' and fathers' social information processing biases and harsh discipline in nine countries. (25th April 2014) - Lansford, Jennifer E.; Woodlief, Darren; Malone, Patrick S.; Oburu, Paul; Pastorelli, Concetta; Skinner, Ann T.; Sorbring, Emma; Tapanya, Sombat; Tirado, Liliana Maria Uribe; Zelli, Arnaldo; Al-Hassan, Suha M.; Alampay, Liane Peña; et al.
Abstract: This study examined whether parents' social information processing was related to their subsequent reports of their harsh discipline. Interviews were conducted with mothers ( n = 1, 277) and fathers ( n = 1, 030) of children in 1, 297 families in nine countries (China, Colombia, Italy, Jordan, Kenya, the Philippines, Sweden, Thailand, and the United States), initially when children were 7 to 9 years old and again 1 year later. Structural equation models showed that parents' positive evaluations of aggressive responses to hypothetical childrearing vignettes at Time 1 predicted parents' self-reported harsh physical and nonphysical discipline at Time 2. This link was consistent across mothers and fathers, and across the nine countries, providing support for the universality of the link between positive evaluations of harsh discipline and parents' aggressive behavior toward children. The results suggest that international efforts to eliminate violence toward children could target parents' beliefs about the acceptability and advisability of using harsh physical and nonphysical forms of discipline.